Developing a prehabilitation program in a collision sport: A model developed within English Premiership Rugby Union football - Meir, R.; Diesel, W.; Archer, E. (Strength and Conditioning Journal, 2007)
Many sports involve contact that can result in significant injury to participants. In addition, by their very nature, the vast majority of sports have inherent injury risksthat can result from the most fundamental of movements, e.g., running, sprinting, accelerating, stepping and changing direction, landing, throwing, etc. However, there is evidence within the literature that it may be possible to reduce the incidence of the most common injuries by the systematic targeting of vulnerable areas of the body. This article outlines a prehabilitation model developed as part of the strength and conditioning program in an English professional rugby union club.